Eastern Asian Population History and Contemporary Population Issues - Suzuki, Toru.; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2019)
This book interprets and explains contemporary population issues from historical and cultural perspectives. These include lowest-low fertility in the Republic of Korea and Taiwan, early population aging in China relative to the developmental level, and various modes of domestic and international migration in the region. The book shows that divergent fertility decline can be attributed to the family patterns established in the pre-modern era in each country. It also examines the diversity of international migration in Eastern Asian countries today is also understood from the long-term historical view.
1. Introduction -- 2. Peasant Society in Eastern Asia -- 3. Fertility Decline and Cultural Pattern -- 4.Population Growth and Economic Growth -- 5. Domestic and International Migrations -- 6. Conclusion.
Keywords: Demography; Population; Sociology, Urban; Urban economics; Emigration and immigration; Population and Demography; Urban Sociology; Urban Economics; Human Migration